Akabara : Rūlarsa Ôpha Īṇḍiyā sīrījhamānna pustakano anuvāda - Malleson, G. B. (George Bruce), 1825-1898 (SAMP early 20th-century Indian books project ;, 1913)
Biography of Akbar, Emperor of Hindustan, 1542-1605.